Termite (Isoptera) survey in urban area in Northern of Rio de Janeiro State, Brazil. (2019)
Most pest termites in urban areas in Brazil are exotic species, but native species are becoming an increasing problem. This study aimed to identify termite species infesting trees and houses in urban areas of Campos dos Goytacazes, in the north of Rio de Janeiro State. Trees in the streets of sixteen neighborhoods were inspected for termites. Inspections and interviews were also conducted to verify the occurrence of termites in houses. Termites were recorded in 17 % of the 1,307 trees surveyed. Coptotermes gestroi was the most frequent species (51% of infested trees), Nasutitermes corniger and Microcerotermes strunckii were present in 38 % and 14 % of infested trees, respectively, and Microcerotermes arboreus was the least common (1 %). Different termite species coexisted in 14 % of the infested trees (n = 31). Termite infestations were recorded in 26% of the surveyed households (n = 1,020). Four species were identified as causing damage: Cryptotermes brevis, C. gestroi, N. corniger, and M. strunckii. The most common species was C. brevis, affecting 133 residences (51 %). C. gestroi and N. corniger were less frequent, but they were responsible for more structural damage than C. brevis, which mainly attacked furniture.